Viral Shedding and Susceptibility to Oseltamivir in Hospitalized Immunocompromised Patients with Influenza in the Influenza Resistance Information Study (IRIS). Issue 6 (August 2015) - Fraaij, Pieter L; Schutten, Martin; Javouhey, Etienne; Burleigh, Laura; Outlaw, Russell; Kumar, Deepali; Boucher, Charles A
Background: Immunocompromised patients are at greater risk of complicated influenza and may be more likely to develop antiviral resistance. This observational sub-study of the Influenza Resistance Information Study (NCT00884117) aimed to study antiviral resistance in immunocompromised patients with influenza and characterize its effect on clinical and virological outcomes. Methods: Eligible immunocompromised patients were aged ≥1 year with a local rapid diagnostic or PCR test positive for influenza ≤96 h after diagnosis and with influenza symptoms. Nasal and throat swabs were taken for RT-PCR analysis on day 1 and then every 3 days until patients were virus-free. Resistance was assessed by mutation-specific RT-PCR, phenotypic susceptibility analysis and Sanger sequencing. Results: Of 42 patients enrolled, 29 (69%) were influenza-positive (RT-PCR) on day 1: 18 adults and 11 children aged 1–12 years. Six patients were severely immunocompromised. On days 3, 6 and 9, most patients tested (18/24, 9/15 and 6/9, respectively) had not cleared the virus. Two of five patients assessed after day 9 continued shedding virus until day 15. H1N1pdm09 viruses harbouring H275Y mutations were detected in post-baseline samples from four patients (aged 52–61 years), one of whom had prolonged viral shedding. No genotypic antiviral resistance was detected in the other 20 treated patients (prevalence of resistance, 17%). Correlation between level of immune compromise and resistance or outcomes could not be assessed. Ten patients (seven influenza-positive) were admitted to intensive care and three died. Conclusions: In these patients with mild/moderate immunocompromise, emergence of oseltamivir-resistant viruses was not common. Severity of influenza symptoms ranged from mild to moderate, but correlation with level of compromise could not be determined.